2015
DOI: 10.1039/c5ta06255a
|View full text |Cite
|
Sign up to set email alerts
|

CdSe quantum dots/molecular cobalt catalyst co-grafted open porous NiO film as a photocathode for visible light driven H2 evolution from neutral water

Abstract: An active noble-metal-free photocathode was fabricated by co-grafting water-soluble thioglycolic acid-stabilized CdSe quantum dots and a molecular cobaloxime catalyst (CoP) through chemical linkage on a p-type open porous NiO film. This photocathode was used as a working electrode in a three-electrode cell, which displayed a photocurrent density up to 110 μA cm −2 at an applied potential of 0 V vs. NHE in 0.1 M Na 2 SO 4 solution at pH 6.8 upon visible light illumination. The comparative studies showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…This was clearly demonstrated by a study which showed the dependence of the yield of HER on the index of Cu 2 O crystallographic plane of being the (111) face more active than the (110) [88]. Beside NiO [77,78,89] and Cu 2 O [90], other oxides [91][92][93] were studied as photocathodes for HER, e.g., the mixed oxides p-CaFe 2 O 4 [94] and p-LaFeO 3 with the latter system having presented an interesting value of hydrogen formation rate (11.5 mmol¨h´1) [95]. Metal sulfide photocathodes like CoS [96], CoS 2 [97,98] [99]), nitrides of semi-and non-metallic atoms (GaN [112] and C 3 N 4 [113]), borides of metals (Co 2 B [114]), arsenides of semi-metallic atoms or non-metals (GaPNAs [115], GaAs [116], AlGaAs [116]), tellurides of metals (CdTe QD [73]), and carbides of semi-metallic atoms (4H-SiC [117], 3C-SiC [118]).…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 94%
See 3 more Smart Citations
“…This was clearly demonstrated by a study which showed the dependence of the yield of HER on the index of Cu 2 O crystallographic plane of being the (111) face more active than the (110) [88]. Beside NiO [77,78,89] and Cu 2 O [90], other oxides [91][92][93] were studied as photocathodes for HER, e.g., the mixed oxides p-CaFe 2 O 4 [94] and p-LaFeO 3 with the latter system having presented an interesting value of hydrogen formation rate (11.5 mmol¨h´1) [95]. Metal sulfide photocathodes like CoS [96], CoS 2 [97,98] [99]), nitrides of semi-and non-metallic atoms (GaN [112] and C 3 N 4 [113]), borides of metals (Co 2 B [114]), arsenides of semi-metallic atoms or non-metals (GaPNAs [115], GaAs [116], AlGaAs [116]), tellurides of metals (CdTe QD [73]), and carbides of semi-metallic atoms (4H-SiC [117], 3C-SiC [118]).…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 94%
“…One of the main concerns at the basis of the development of PECs for water splitting [71] which produce molecular H 2 at the (photo)cathode and O 2 at the (photo)anode is the replacement of precious metals like Pt or Ru photoelectrocatalysts with durable semiconducting electrodes of p-type based on cheaper metal oxides, phosphides and sulfides/disulfides or Si, in order to photoactivate HER (hydrogen evolution reaction). Due to the wide employment in p-DSCs, NiO photocathodes have been considered also for the application of photoelectrochemical generation of H 2 in a variety of sensitization schemes and surface decorations (Figures 11-14) [36,[72][73][74][75][76][77][78][79].…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a type of electrode modification consists mainly in the impartation of additional optical absorption [38][39][40][41][42][43][44][45][46][47][48][49] and photoelectroactivity to NiO in the NIR-Vis range, i.e., in a spectral range of lower energies with 2 of 18 respect to the intrinsic optical absorption of pristine NiO (typically in the near ultraviolet (UV)) [50]. Dye sensitization of nanostructured p-type NiO is finalized principally to the realization of devices, such as dye-sensitized solar cells of p-type (p-DSCs) [51][52][53][54][55][56][57][58][59], light-fueled electrolyzers for hydrogen generation [5,[60][61][62][63][64][65], and photoelectrochemical reactors for carbon dioxide reduction [66,67]. Because of these finalities, the study of dye-sensitized electrodes is usually aimed at the analysis of the light absorption properties and at the determination of the efficiency of photoelectrochemical conversion in the process of interest.…”
Section: Introductionmentioning
confidence: 99%